RESEARCH ON TECHNOLOGY DEVELOPMENT FOR FISHING VESSELS IDENTIFICATION BY SATELLITE REMOTE SENSING - STATUS IN DEVELOPED COUNTRIES AND JAPANESE PATROL SYSTEM - T. Moriyama; H. Tameishi; J. Suwa; S. Kanno; Y. Sugimori (BRIN, 2004)
Current status and trends ov vessel detection, identification technology development and application in major countries were surveyed. According to increasing the number of foreign poaching and suspicious vessels intrusion into EEZ, patroliling by vessel and airplane does not satisfy the needs because of narrow coverege and observation frequncey. The satellite monitoring by SAR and optical sensor has been studied and partially used, but there are several disavantages such as observation frequncy, geometric occuracy and weather dependence to adopt for operational use. This paper describes an optimize system for vessel detection and identification by combining patrolling vessel, airplane and satellite.